(untitled) (El Taco en la Brea, 2025)
The «critical function» admits multiple supports, not exclusively the article or the book that is formulated from previous texts. In the typology in which criticism is manifested, the essay is in the first line, beside some lateral forms of exercising judgment such as the chronicle, the intellectual correspondence, the prologue and the paratextual redoubts of the back cover and the flap, when their will exceeds that of the mere sale of copies. This article deals with the prologue as a critical avatar and proceeds to a selection of prologues that have not only been recognized as a critical alternative but have sometimes taken away relevance from the very text to which they precede. This circumstance confirms that criticism is an independent genre, which transits morphological varieties and whose formulations admit to be linked through comparative strategies.